Les compléments et produits alimentaires chez les sportifs : Consommation, risques, importance du conseil officinal - AICHOUR , Alaaeddine; AMRANE , Salah Eddine; DJAHEL , Islam; MEKHALFIA , Raid Islam; BOUHEDADJA , Zahia (Encadrant) (Université Sétif1 Ferhat Abbas. Faculté de Médecine. Département de Pharmacie, 2024)
The aim of our work is to study the consumption of food supplements in the sports environment(bodybuilding) and their effectiveness on their health. We conducted our study among consumers of nutritional supplements among athletes wilaya de MSILA, and according to the results, the age of consumers varies from 15 to 35 years. The study confirms that 59% are between 20 and 35 years old, while 21% are between 15 and 20 years old. Our results showed that the rate of consumption of nutritional supplements among athletes is very high, and most of them state that their goal is to increase their muscle mass. The results also showed that a large number of consumers achieved a positive result. In conclusion, it is essential to benefit from a follow-up provided by coaches or dieticians in order to avoid the risks associated with an overconsumption of dietary supplements among bodybuilders. In addition, regular physical activity is strongly recommended to take full advantage of the benefits offered by these supplements.
الهدف من عملنا هو دراسة استهالك المكمالت الغذائية في البيئة الرياضية (كمال األجسام) وفعاليتها على صحتهم. أجرينا دراستنا بين مستهلكي المكمالت الغذائية بين الرياضيين في والية المسيلة، ووفقا للنتائج، يتراوح عمر المستهلكين من 15إلى 35عا ًما. تؤكد الدراسة أن ٪59تتراوح أعمارهم بين 20و 35 عا ما، بينما تتراوح أعمار ٪21بين 15و 20عا ما. أظهرت نتائجنا أن معدل استهالك المكمالت الغذائية بين الرياضيين مرتفع للغاية، ويذكر معظمهم أن هدفهم هو زيادة كتلة عضالتهم. كما أظهرت النتائج أن عدد ا كبي ًرا من المستهلكين حققوا نتيجة إيجابية. في الختام، من الضروري االستفادة من المتابعة التي يقدمها المدربون أو أخصائيو التغذية لتجنب المخاطر المرتبطة باالستهالك المفرط للمكمالت الغذائية بين العبي كمال األجسام. باإلضافة إلى ذلك، يوصى بشدة بالنشاط البدني المنتظم لالستفادة الكاملة من المزايا التي تقدمها هذه المكمالت
Keywords: Complément alimentaire; sportif; bodybuilders; consommation; risque; wilaya de MSILA.